The Keepers of the Gate: The Inequality of Property Ownership During the Winnipeg Real Estate Boom of 1881-82 - Burley, David (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
Recent scholarship has identified inequality in real property ownership as a constant feature of urban social structure. This study of Winnipeg during the boom of 1881-82 examines the reproduction of that inequality in terms of the strategies employed by major landowners to profit in an inflationary real estate market. Such men preferred to invest in rental properties, especially commercial accommodation. Best able to do so were those members of the bourgeoisie who, by virtue of their early arrival, had acquired cheap vacant land, the sale of which financed their acquisition of rental units. Thus, the reproduction of inequality involved the conversion of prior advantage in one real estate market, that for vacant land, into an advantage in a second market, that for rental accommodation.